Right N170 modulation in a face discrimination task: An account for categorical perception of familiar faces - CAMPANELLA, S.; HANOTEAU, C.; DÉPY, D.; ROSSION, B.; BRUYER, R.; CROMMELINCK, M.; GUÉRIT, J.M. (Psychophysiology, 2000)
Behavioral studies have shown that two different morphed faces belonging to the same identity are harder to discriminate than two faces stemming from two different identities. The temporal course of this categorical perception effect has been explored through event-related potentials. Three kinds of pairs were presented in a matching task: (1) two different morphed faces representing the same identity (within), (2) two other faces representing two different identities (between), and (3) two identical morphed faces (same). Following the second face onset in the pair, the amplitude of the right occipitotemporal negativity (N170) was reduced for within and same pairs as compared with between pairs, suggesting an identity priming effect. We also observed a modulation of the P3b wave, as the amplitude of the responses for within pairs was higher than for between and same pairs, suggesting a higher complexity of the task for within pairs. These results indicate that categorical perception of human faces has a perceptual origin in the right occipitotemporal hemisphere.